Parmodel: a web server for automated comparative modeling of proteins - Uchoa, H. B.; Jorge, G. E.; Da Silveira, NJF; Camera, J. C.; Canduri, F.; De Azevedo, W. F. (Elsevier B.V., 2004)
Parmodel is a web server for automated comparative modeling and evaluation of protein structures. The aim of this tool is to help inexperienced users to perform modeling, assessment, visualization, and optimization of protein models as well as crystallographers to evaluate structures solved experimentally. It is subdivided in four modules: Parmodel Modeling, Parmodel Assessment, Parmodel Visualization, and Parmodel Optimization. The main module is the Parmodel Modeling that allows the building of several models ford a same protein in a reduced time, through the distribution of modeling processes on a Beowulf cluster. Parmodel automates and integrates the main softwares used in comparative modeling as MODELLER, Whatcheck, Procheck, Raster3D, Molscript, and Gromacs. This web server is freely accessible at http://www.biocristalografia.df.ibilce.unesp.br/tools/parmodel. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: bioinformatics; comparative modeling; structural analysis